Pendampingan Pembelajaran Tahsin Melalui Surat Al-Zalzalah: Peningkatan Kualitas Bacaan Al-Qur'an di Kalangan Santri - Tifani, Dinda Femila Aprilia; Munir, Dede Rizal; Setiawan, Usep (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The tahsin mentoring program aims to improve the quality of Al-Qur'an recitation with a focus on Surah Al-Zalzalah. This study employs a descriptive qualitative method with an action research approach. The results indicate that tahsin learning based on Surah Al-Zalzalah positively impacts the fluency, tajwid, and makharijul huruf of the students. Through the talaqqi method and repeated practice, students can enhance their understanding and mastery in reading the Al-Qur'an correctly and accurately.